Penerapan Hukum Secara Gradual Melalui Konsep Makkiyah dan Madaniyyah - Muhammad Maksum (Hikmah: Journal of Islamic Studies, 2018)
The concept of the Makkiyyah and Madaniyyah is not sufficiently understood as the classification of verses based on time, place, or substance of the verse revealed. The concept of Makkiyah and Madaniyyah also contains the graduation of society development and the determination of law. Society development starts from an uncivilized society towards civilized society (Medina). The graduation of law starts from the conception of a general arrangement towards a more detailed and specific arrangement along with the progress of human growth. The conception of the Makkiyyah and Madaniyyah is thus a legal and social conception, in the sense of showing the existence of graduation. Keywords: Makkiyyah, Madaniyyah, Preaching, Gradually Konsep Makkiyyah dan Madaniyyah tidak cukup dipahami sebagai klasifikasi ayat berdasarkan waktu, tempat, ataupun substansi dari ayat yang diturunkan. Konsep Makkiyah dan Madaniyyah mengandung pula graduasi pembangunan masyarakat dan penetapan hukum. Pembangunan masyarakat berawal dari masyarakat yang tidak beradab menuju masyarakat beradab (madinah). Graduasi hukum berawal dari konsepsi pengaturan umum menuju pengaturan yang lebih detil dan spesifik seiring dengan majunya pertumbuhan manusia. Konsepsi Makkiyyah dan Madaniyyah dengan demikian merupakan konsepsi hukum dan sosial, dalam arti menunjukkan adanya graduasi. Kata Kunci: Makkiyyah, Madaniyyah, Dakwah, Gradual